Diversity and antimicrobial activity of endophytic fungi isolated from Cephalotaxus hainanensis Li, a well‐known medicinal plant in China. (29th September 2015) - Yang, H.R.; Hu, X.P.; Jiang, C.J.; Qi, J.; Wu, Y.C.; Li, W.; Zeng, Y.J.; Li, C.F.; Liu, S.X.
Abstract About 1051 endophytic fungi were isolated from leaves, branches, barks and stems of Cephalotaxus hainanensis Li from four sites in Hainan, China. The fungi were identified as 21 genera by morphology and ITS sequences. One dominant species was Phomopsis quercella in Hainan Tropical Botanical Garden and Bawangling Nature Reserve, with relative frequency of 42·06 and 34·88% respectively. Another dominant species was Colletotrichum boninense in Wuzhishan and Jianfengling Nature Reserves, with relative frequency of 36·84 and 46·97% respectively. Among the selected 21 endophytic fungi, 17 strains (80·95%) had activity against at least one pathogenic bacteria, and 14 strains (66·67%) exhibited activity against at least one fungal pathogens. Neonectria macroconidialis showed strong inhibition against Staphylococcus aureus (inhibition zone being 20 mm), Bacillus subtilis (14 mm) and Streptococcus agalactiae (28 mm). Xylaria sp. showed strong inhibition against Escherichia coli (20 mm), Rhizoctonia solani (20 mm) and Sclerotinia sclerotiorum (17 mm). Verticillium bulbillosum showed great activity against Strep. agalactiae (32 mm) and Fusarium oxysporum (22 mm). These endophytic fungi showed potentials in medicine development. Significance and Impact of the Study Endophytic fungi from medicinal plants are an important source of novel and viable drugs. Cephalotaxus hainanensis Li is well known for leukaemia treatment and its endophytic fungi were isolated to investigate the diversity and antimicrobial activity. It was found that Ce. hainanensis Li had rich endophytic fungi, and some fungi showed strong antimicrobial activity against certain pathogens. These fungi can be used in medicine development.